BEHAVIOR OF COMPOSITE COLUMNS UNDER LATERAL LOADING - طوالو, علي (Latakia University Journal -Engineering Sciences Series, 2024)
Composite columns are widely used in building structures, especially high-rise ones. They are considered of great importance because they depend on the principle of sharing between two materials that work together in one structural element while taking advantage of the advantages of each of them, as the tensile strength of steel and the pressure of concrete. Composite columns are characterized by their high rigidity and good resistance, in addition to their plasticity property in cases of static and dynamic loading. The presence of concrete helps in resisting axial loads in addition to resisting lateral buckling and local buckling of the steel section. The concrete also contributes to protecting the steel section from fire and weather factors if the concrete is completely encased in the section. To document the model, a numerical model was created using the ABAQUS program, identical to the experimental model tested by researchers Cristina Campian, Zsolt Nagy. The comparison included the response of the analytical and experimental model represented by the force-displacement curve, and the agreement rate exceeded 90%. The numerical model was invested to study the behavior of four models of Composite columns under the influence of lateral loads. In the next stage, a comparative study was conducted of a building designed with reinforced concrete columns and then replacing them with Composite columns of the second model (IPE). The results have shown that the use of Composite columns is more efficient than reinforced concrete columns in terms of stiffness and resistance, and contributes to the same performance of reinforced concrete columns with sections smaller than the cross-sectional area of the longitudinal reinforcement bars used, which reflects positively on reducing dead loads and thus the economic cost and seismic forces in high-rise buildings.